2021
DOI: 10.2147/ndt.s315653
|View full text |Cite
|
Sign up to set email alerts
|

Cariprazine: Patients with Treatment-Resistant Schizophrenia

Abstract: Schizophrenia is a chronic relapsing and remitting disorder associated with significant impairments in social and vocational functioning and a shortened lifespan, and it is a disabling psychiatric brain syndrome whose phenotype is characterized by three core symptom domains: positive symptoms, such as delusions and hallucinations, negative symptoms, which include lack of motivation and social withdrawal, and cognitive impairment. Moreover, patients with schizophrenia have severe problems with personal and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
3
23
0
2
Order By: Relevance
“… 38 45 As can be seen in Table 2 , clozapine augmentation with cariprazine for negative symptoms has not been widely studied, with evidence limited to case reports and case series. 28 , 46 Nevertheless, the current evidence provides ground for cautious optimism. Consistent with our study, a recent case series by Berardis et al demonstrated the effectiveness of cariprazine in combination with clozapine for the treatment of residual negative symptoms.…”
Section: Discussionmentioning
confidence: 95%
“… 38 45 As can be seen in Table 2 , clozapine augmentation with cariprazine for negative symptoms has not been widely studied, with evidence limited to case reports and case series. 28 , 46 Nevertheless, the current evidence provides ground for cautious optimism. Consistent with our study, a recent case series by Berardis et al demonstrated the effectiveness of cariprazine in combination with clozapine for the treatment of residual negative symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Many patients experienced intolerable side effects induced by other antipsychotics, therefore cariprazine was initiated due to its favorable safety profile. Three patients experienced psychomotor retardation ( n = 3), and in case of one patient ( case 2 ) ( 35 ), it got so severe that she became fully bedridden. Furthermore, weight gain ( n = 3) and the development of metabolic syndrome ( n = 3) were problematic for patients; one of them ( case 15 ) ( 42 ) gained 30 kg after the first year of taking olanzapine, causing increases in triglyceride and cholesterol levels.…”
Section: Resultsmentioning
confidence: 99%
“…In case of cariprazine, switching from another antipsychotic can be beneficial if there has been no or only partial response to positive or negative symptoms (27,31,32,35,37,41,43), if the patient suffers from side effects (27,(34)(35)(36)42) that are less common with cariprazine such as weight gain, hyperprolactinemia, sexual disturbance or sedation (44) or if the patients has been prone to non-adherence or substance abuse (29,35).…”
Section: Switching From Another Antipsychotic To Cariprazinementioning
confidence: 99%
“…Fast titration involves an increase of 1.5 mg/day each day or every second day until the target dose is achieved, as seen in the short-term clinical trials ( 20 , 21 , 23 ). This or similar strategy was utilized in several cases ( 31 , 33 – 35 , 37 , 40 , 41 , 43 ), where 3.0 mg/day dose was introduced within less than a week after the beginning of the treatment. In these cases, most of the patients exhibited considerable psychotic symptoms with or without negative symptoms and weight gain problems caused by previous medication.…”
Section: Cariprazine a Third-generation Antipsychotic Agentmentioning
confidence: 99%